Policy innovation and maintaining influential local governments - Kulaç, Onur, 1984-; Akman, Çiğdem (IGI Global Scientific Publishing, 2026)
"To understand the complexities of local governance globally, it is essential to examine the structures of countries with diverse local government systems, analyze their policy processes, and compare their approaches. In doing so, the role of policy innovation and the influence of local governments in shaping effective governance can be better appreciated"-- Provided by publisher.